ClinicaHy important enzymes in Jamunapari and Marwari goats* - MAHAWAR, MANISH; JAIN, A K; KUMAR, PUNEET (The Indian Journal of Animal Sciences, 2014)
Serum samples (176) from Jamunapari and Marwari bucks were evaluated to estimate activities of clinically important enzymes, viz, acid phosphatase (ACP), alkaline phosphatase (AKP), glutamate-oxaloacetate transaminase (GOT), glutamatepyruvate transaminase (GPT) and lactate dehydrogenase (LDH), The overall mean values were 1.23Â±0,04 King Armstrong’s Units/dl, 11.75Â±0.42 King Armstrong’s Units/dl, 51 ,62Â±0,70 Karmen’s Units/ml, 16,84Â±0.50 Karmen’s Units/ml and 308.52Â±6,71 International Units/litre respectively, The activity of AKP was significantly (P<0.05) higher in Jarnunapari breed (13.91Â±0,63 King Armstrong’s Units/dl) than that in Marwari breed (9.58Â±0.45 King Armstrong’s Units/dl). The activities of other enzymes were not significantly (P>0.05) different between the breeds.